2020
DOI: 10.1590/0103-8478cr20191010
|View full text |Cite
|
Sign up to set email alerts
|

Narcotic detection dogs: an overview of high-performance animals

Abstract: Considered one of the best odor detectors, dogs go through a rigorous selection and training process. Based on learning theories, modern techniques are used for dog training, respecting individual characteristics, efficiency, and well-being. Since narcotics detection work is perceived as a “play” for the dog, in practice, this promotes a high use rate in the service. The performance of handlers influences the work of the dogs, and well-trained and well-run dogs must work comfortably and accurately. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Also, it should be taken into consideration that the wrong alert and misses may not always be a dog error but may be due to human faults. Wrong alerts that resulted from insufficient training of dogs are due to the actions of handlers (Hunter, 2002;Gazit e al., 2005;Lit et al, 2011;Duranton and Horowitz, 2019;Jantorno et al, 2020), so dog's human-directed communitive behavior could affect individual experience (Marshall-Pescini et al, 2009). Moreover, Jezierski et al (2014) proposed that handlers' stress may affect dogs' activity, when they understood that trials attempts were certification, the dogs made more wrong indication and so fewer true alerts and longer searching period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it should be taken into consideration that the wrong alert and misses may not always be a dog error but may be due to human faults. Wrong alerts that resulted from insufficient training of dogs are due to the actions of handlers (Hunter, 2002;Gazit e al., 2005;Lit et al, 2011;Duranton and Horowitz, 2019;Jantorno et al, 2020), so dog's human-directed communitive behavior could affect individual experience (Marshall-Pescini et al, 2009). Moreover, Jezierski et al (2014) proposed that handlers' stress may affect dogs' activity, when they understood that trials attempts were certification, the dogs made more wrong indication and so fewer true alerts and longer searching period.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the poor performance in odor detection, temperament and training issues could have a minor role in those failures. Moreover, the dog's welfare is valuable to the training and formation of a drug detection dog ( Jantorno et al, 2020) The present study was undertaken to assess the effect of dogs , breed, searching site, and training experience on the detection performance of narcotics.…”
Section: Introductionmentioning
confidence: 99%
“…Detection dogs have been trained to find a wide variety of hidden and cryptic targets such as invasive insects and weeds (Aviles‐Rosa, Nita, et al, 2022; Hanigan & Smith, 2014), narcotics (Furton et al, 2002; Jantorno et al, 2020), explosives (Aviles‐Rosa, McGuinness, et al, 2021; Lazarowski et al, 2021; Lazarowski & Dorman, 2014) and even missing persons (Jinn et al, 2020). In doing so, dogs are tasked to search a given environment to find and respond to their trained target odor, perhaps not unlike animals that must search for prey and productive areas to forage.…”
Section: Figurementioning
confidence: 99%
“…Narcotic Detection Dogs can be trained to detect drugs such as synthetic cathinone (amphetamine) and have shown that they can be quickly prepared to detect new threats (ethylene and α-PVP amphetamine) in a matter of weeks (13). NDDs are considered highly accurate, low-cost within their economic context compared to other police-border protection priorities, and reliable real-time narcotics detection tools, increasing the efficiency and speed of inspection at customs posts and frontiers (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%